Muscular factor in the development of musculoskeletal pain. Treatment options - A. I. Isaikin; T. I. Nasonova (Неврология, нейропсихиатрия, психосоматика)
The importance of the muscular factor, which is traditionally considered in myofascial pain syndrome (MFPS), in the development and maintenance of musculoskeletal pain (MSP) is actively discussed. The hypothesis of the leading role of myofascial trigger points (MTPs) in muscle pain remains debatable. Probably, muscle pain is secondary to the underlying disease. The MTP phenomenon is considered as an area of secondary hyperalgesia resulting from neurogenic inflammation in muscles that were not initially structurally and physiologically damaged. According to these ideas, MFPS is a complex form of neuromuscular dysfunction, which is represented by soft tissue damage with the development of peripheral and central sensitization as a result of neurogenic inflammation, changes in the functioning of limbic system structures. MFPS is a clinical diagnosis, based on the presence of painful spasmodic muscles, painful muscle indurations, active trigger points with zones of reflected pain. The sensitivity and specificity of clinical tests for MFPS have not been determined. Currently, there are no proven universally accepted criteria (such as biomarkers, electrophysiological evaluation, imaging, diagnostic blocks, etc.) for objectifying or quantifying MTPs. Nonpharmacological interventions with the most proven effectiveness include therapeutic exercises and psychotherapeutic techniques, other methods are of secondary importance. The effectiveness of aceclofenac (Aertal®) and the muscle relaxant tolperisone (Mydocalm®) in the of MSP treatment is discussed. It is noted that a new form of tolperisone – Mydocalm®-Long 450 mg - can reduce the frequency of drug administration, provide a proven and predictable therapeutic effect, and increase treatment adherence.